Ionic liquids–lignin combination: an innovative way to improve mechanical behaviour and water vapour permeability of eco-designed biodegradable polymer blends. Issue 3 (5th December 2014) - Livi, Sébastien; Bugatti, Valeria; Marechal, Manuel; Soares, Bluma G.; Barra, Guilherme M. O.; Duchet-Rumeau, Jannick; Gérard, Jean-François
Abstract : In this work, the potential use of lignin combined with ionic liquids (ILs) has been investigated on the final properties of biodegradable polymer blends. Abstract : In this work, the potential use of lignin combined with ionic liquids (ILs) has been investigated on the final properties of biodegradable polymer blends. Poly(butylene-adipate-co-terephtalate)–polylactide–lignin (PBAT–PLA–Lig) were melted blending in one pot by using phosphonium ionic liquids as new additives. The effect of incorporating 16 wt% of lignin and PLA and 1 wt% of ILs into PBAT matrix has been explored on the mechanical behaviour, the water vapour permeability, the thermal stability as well as the morphologies of PBAT–PLA–Lig–IL blends. In all cases, the lignin–ionic liquid combination leads to a good mechanical performance coupled with a dramatic increase in water barrier properties. In addition, transmission electron microscopy (TEM) analysis has been used to investigate the influence of ILs on the different morphologies of these sustainable polymer blends.